2007
DOI: 10.1002/ejic.200700304
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of CO by Mo[N(R)Ar]3 Complexes

Abstract: The reaction of MoL3 [L = NH2 and N(tBu)Ar] with CO was explored using DFT in order to rationalize why CO cleavage is not observed experimentally for this system in contrast to the corresponding N2 reaction which results in spontaneous cleavage of the N–N bond. The binding of CO to MoL3 was found to be both kinetically and thermodynamically favored over the binding of N2, with the formation of the encounter complex, L3Mo–CO, calculated to be without barrier and exothermic. While the overall reaction to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…[48,52] For the model system, the energies of the reactant and product species are reported for both the minimum energy structures and for structures in which the Mo À N ax distance was fixed to 2.4 in order to mimic the constraints of the ligand straps. Full DFT single point calculations were also carried out on the QM/MM optimised geometries of the full ligand system.…”
Section: Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…[48,52] For the model system, the energies of the reactant and product species are reported for both the minimum energy structures and for structures in which the Mo À N ax distance was fixed to 2.4 in order to mimic the constraints of the ligand straps. Full DFT single point calculations were also carried out on the QM/MM optimised geometries of the full ligand system.…”
Section: Complexmentioning
confidence: 99%
“…A similar trend was observed for the corresponding three-coordinate MoL 3 (L = NH 2 , NA C H T U N G T R E N N U N G (tBu)Ar) system when the model NH 2 ligands were replaced by the bulky NA C H T U N G T R E N N U N G (tBu)Ar groups in the full ligand system. [48,52] The effect of ligand bulk is especially evident for the intermediate dimer which is destabilized by 105 kJ mol À1 relative to the optimized model system and even further when the MoÀN ax bond is constrained, bringing it 14 kJ mol À1 above the products in energy. The small exothermicity of the N À N cleavage step differs from the calculations of Cui et al [22] for which the same step was calculated to be endothermic by 42 kJ mol…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The results in Table 3 show a clear correlation between the overall enthalpy of reaction and the M À N bond strength: as the M À N bond in the product becomes stronger, the overall reaction enthalpy progressively increases. We have observed this correlation in our earlier studies of three-coordinate systems, [7] and it formed the premise on which we initially optimised the cleavage reactions associated with N 2 , CO, CS, CN À and NO, [37][38][39][40] but on the basis of the data in Table 3, this trend is clearly more general. Overall, greater enthalpies and M À N bond strengths are calculated for the Nb complexes, in agreement with the results of our earlier bond energy study, which showed that the M À N …”
mentioning
confidence: 71%
“…This particular system has been the subject of numerous experimental and mechanistic studies relating not only to N 2 but also to N 2 O, NO, NO 2 , CO, CS, CN -, CS 2 , OSMe, P 4 and SO 2 . [21][22][23][24][25][26][27][28][29][30][31][32][33][34] In all of these cases the catalyst shows high activity, but particular note was made in regard to carbon dioxide. It is remarkably inactive, in fact the Laplaza-Cummins catalyst will not even bind to CO 2 .…”
Section: Introductionmentioning
confidence: 99%